Efficacy and safety of G-Lite® cream (oxyresveratrol based combination) with Cristello® sunscreen in hyperpigmentation management - Chandrashekar, B. S.; Roopa, M. S.; Lalchandani, Rajesh; Dawre , Shilpa (International Journal of Research in Dermatology, 2025)
Background: Hyperpigmentation is a prevalent concern in skin of color, characterized by excessive melanin production due to inflammation, UV exposure, hormonal fluctuations, or dermatological conditions. Individuals with Fitzpatrick skin types IV-V are more susceptible to persistent pigmentary disorders such as melasma and post-inflammatory hyperpigmentation (PIH), necessitating cautious treatment to avoid hypopigmentation or worsening pigmentation. Conventional depigmenting agents often pose safety concerns, leading to increased interest in botanical and cosmeceutical alternatives with superior tolerability. This study evaluates the efficacy and safety of G-Lite® (Oxyresveratrol based combination) cream in combination with Cristello® sunscreen for treating hyperpigmentation. Methods: A prospective, open-label, non-comparative study was conducted. Thirty adults (18–45 years) with epidermal hyperpigmentation were enrolled and followed up for 12 weeks. Participants applied G-Lite® cream at night once daily (OD) and Cristello® sunscreen thrice daily. Melanin and erythema indices were assessed using Dermacatch at baseline (visit 1), week 6 (visit 2), and week 12 (visit 3). Clinical photographs and patient satisfaction were recorded. Results: Melanin levels decreased by 30–33% across facial regions, while erythema reduced by 17–22%, indicating efficacy with good tolerability. Physician assessments showed that 73% of participants achieved at least a 26% pigmentation reduction. Patient satisfaction closely aligned with clinical outcomes. No adverse effects were reported. Conclusions: G-Lite® cream effectively reduces hyperpigmentation in skin of color with minimal irritation. Its botanical formulation offers a promising, safer alternative to conventional depigmenting agents.